Answer :

We have


and


Lets simplify these equations. Assuming 1/x = z, we can rewrite them,



5z + 6y = 13 …(i)



3z + 4y = 7 …(ii)


To solve these equations, we need to make one of the variables (in both the equations) have same coefficient.


Lets multiply eq.(i) by 3 and eq.(ii) by 5, so that variable z in both the equations have same coefficient.


Recalling equations (i) & (ii),


5z + 6y = 13 [×3


3z + 4y = 7 [×5



- 2y = 4


y = - 2


Substitute y = - 2 in eq.(i)/eq.(ii), as per convenience of solving.


Thus, substituting in eq.(ii), we get


3z + 4( - 2) = 7


3z – 8 = 7


3z = 7 + 8


3z = 15


z = 5


Thus, z = 5 and y = - 2


As z = 1/x,


5 = 1/x


x = 1/5


Hence, we have x = 1/5 and y = - 2


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve each of theRS Aggarwal - Mathematics

If 2x – 3y = 7 anRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics